Helical Pedagogical Model for the Teaching and Learning of Chemistry in University Settings - Rojas Ulate, Marcos (2021)
Scientific university pedagogy has several shortcomings related to the educational system that affect students’ professional growth. Due to this situation, a new pedagogical model is required to solve these problems and limitations. Helical pedagogy establishes the necessity to set up an emotional, retroactive, interconnected, and gradient education to help students apply knowledge during every single moment of their labor or academic life. Through the stimulation of some mental processes related to human beings during their entire life (childhood or adulthood), knowledge can be created faster and in an easier way. Still, also a solid platform is required which contributes to the helical learning, for instance, individual projects, dynamic classes with two or more professors, and, of course, the avoidance of lectures and traditional evaluation methods. These changes do not mean that the quality of the educational system should be lower. The only objective of this new pedagogical method is to improve the way that chemistry is being learned by the students and also to make them more confident about their potential. This will happen if they change their perspective and vision about their studies and professional careers. This helical model seeks to transform the way to understand chemical pedagogy by using theoretical and praxeological proposals applicable in any context around the world.